Mapping Evacuation Routes During a Tsunami Using the A* Algorithm - Suchyan Hanafi; Ilham Dangu Rianjaya; Lilis Harianti Hasibuan (CIB Nusantara, 2025)
As an archipelago, West Sumatra is prone to tsunamis due to its location between three major tectonic plates. One of the tsunami-prone areas in West Sumatra province is Padang City, specifically Lubuk Buaya Subdistrict, because it borders directly on the sea, an active underwater volcano, and earthquakes on the seabed. To address this issue, the A* algorithm was applied to find evacuation routes from Pasir Jambak. The data used in this study were secondary data in the form of coordinate points and travel distances obtained from Google Earth, which were used in a weighted graph. The results of the study were obtained the shortest evacuation route from the origin point to the nearest destination point with a total distance of 2,751 m (2.7 km).